ADHERENCE TO THE NICE HEAD INJURY GUIDELINES 2007 AND 2014 IN ANTICOAGULATED PATIENTS. Issue 9 (14th August 2014) - Kuczawski, Maxine; Mason, Suzanne; Stevenson, Matt; Holmes, Michael; Teare, Marion D; Ramlakhan, Shammi; Goodacre, Steve; Morris, Francis; Harper, Rosemary
Abstract : Objectives & Background: Until January 2014, The National Institute of Clinical Excellence (NICE) Head Injury Guidelines (CG56) issued to clinicians advised anticoagulated patients with a head injury should only receive CT imaging if loss of consciousness or amnesia was experienced. These guidelines have recently been updated to advise CT imaging for all anticoagulated patients. We aimed to investigate how closely the 2007 guidelines were followed and whether the guideline update will mean considerable changes to existing practice. Methods: Data was analysed from the AHEAD Study, a large prospective observational multicentre study involving 33 emergency departments in England and Scotland. Within the cohort of anticoagulated patients, those that complied with the NICE guidelines (2007 and 2014) were identified and categorised into 3 groups depending on the NICE CT imaging advice a) <1 hr, b) <8 hrs and c) all patients. The symptoms, treatment and outcomes of these patients were described and compared with actual clinical practice. Results: Applying NICE 2007 criteria to the 3534 patients, 779 (22%) patients were identified as eligible candidates for CT imaging—within 1hr, 558 (72%) patients and within 8hrs, 221 (28%) patients. Of the eligible patients, 82% (n=641) actually did have a CT head scan of which 17% (n=111) had a significant head injury-related finding. Adherence in the time to CT was achieved for 16% within 1hr and 90% within 8hrs (Mean 285 and 243 minutes respectively). Neurosurgery was performed in 14 (1.8%) patients and 27 (3.5%) patients died of a head injury-related death. Of those patients that did not fulfil the NICE 2007 criteria (n=2755), 54% (n=1473) had CT imaging on average 431 minutes after ED attendance. A significant CT finding was found in 5.9% (n=87) patients, neurosurgery performed in 5 (0.2%) patients and 15 (0.5%) patients died of a head injury-related death. Applying the updated NICE 2014 advice which states all anticoagulated patients should receive CT imaging, found only 60% (n=2114) of this cohort received it. Conclusion: The majority of patients that fulfilled the NICE 2007 criteria did have CT imaging performed (82%). However, a significant number of patients not fulfilling the criteria also had CT imagining performed. Overall, 60% of the anticoagulated patient cohort had CT imaging, this will need to increase considerably to follow the updated NICE 2014 guidelines of CT imaging for all patients.